Effect of the Dark Tetrad on Emotional Intelligence - Sokić, Katarina (Primenjena psihologija, 2022)
The main aim of this study was to investigate the relationships between Dark Tetrad traits (Machiavellianism, narcissism, psychopathy and sadism) and ability emotional intelligence dimensions – self-emotion appraisal, others’ emotion appraisal, use of emotion and regulation of emotion. The Wong and Law Emotional Intelligence Scale, Short Dark Triad and Assessment of Sadistic Personality were applied to a sample of 322 participants from the general population (63% women) of Croatia. Results showed that both psychopathy and sadism had negative relations with emotional intelligence. Sadism showed significant effects on self-emotion appraisal, others’ emotion appraisal, and use of emotion dimensions, while psychopathy showed significant effect on regulation of emotion. Machiavellianism negatively correlated to a weaker degree with self-emotion appraisal and others’ emotion appraisal, but it showed no significant effects on emotional intelligence dimensions in regression analysis. Narcissism showed positive effects on EI as a whole, use of emotion and self-emotion appraisal. The results highlighted the importance of the dark traits in the explanation of emotional intelligence and showed that the dark traits are differently associated with emotional intelligence dimensions.